2022
DOI: 10.1109/access.2022.3170409
|View full text |Cite
|
Sign up to set email alerts
|

Double-Differential Amplifier for sEMG Measurement by Means of a Current-Mode Approach

Abstract: This work proposes a Double Differential (DD) amplifier topology which exploits the advantages of the current-mode approach. DD amplifiers are useful as front-ends in standalone active electrodes for superficial electromyography (sEMG) wearable applications and electroneurography (ENG) measurement devices. Front-ends for these applications need to attain low noise, high common-mode rejection ratio, and high input impedance to measure biopotential signals and can further benefit from low power operation, a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In previous work by the authors [26], an extension of the CCII-based instrumentation amplifier was found, highlighting that a passive network could perform the doubledifferential calculation in current mode. A generalization of this characteristic can be found by examining the network in Figure 3a, for which the Thévenin equivalent impedance of the electrodes can be found for the case Z 2 = Z 3 .…”
Section: Circuit Topologymentioning
confidence: 85%
See 2 more Smart Citations
“…In previous work by the authors [26], an extension of the CCII-based instrumentation amplifier was found, highlighting that a passive network could perform the doubledifferential calculation in current mode. A generalization of this characteristic can be found by examining the network in Figure 3a, for which the Thévenin equivalent impedance of the electrodes can be found for the case Z 2 = Z 3 .…”
Section: Circuit Topologymentioning
confidence: 85%
“…However, in order to realize a board-level implementation, instead of a CCII circuit, which is not easy to find as an off-the-shelf component, a surrogate has been used. In particular, noting that since the output taken from the CCII amplifier is the voltage on impedance Z o (due to the output current from the CCII Z node), we can achieve the same result by using an operational amplifier (OA) connected as in Figure 4a, which implements an equivalent function to the CCII [26]. Indeed, thanks to the virtual ground property, the voltage v i at the OA non-inverting input is accurately replicated at the OA inverting input, as occurs in the CCII at nodes Y and X.…”
Section: And Proof-of-concept Implementationmentioning
confidence: 95%
See 1 more Smart Citation